Displacement in Colombia and its various views - Cabrera Suárez, Lizandro Alfonso (DIXI, 2017)
Theme and scope: from day to day the displaced are accompanied by contempt and umiliation. The effect it has is perhaps not appreciated by the inhabitant of Cali, who, on the contrary, sees them as a problem and a social burden. However, their quality of life is opposed to the profitable business of those who now occupy their lands. Characteristics: the displaced are forced to camouflage themselves in society and leave behind production in the countryside, change their lives and learn to earn their living. Societies transform, especially in Colombia for being a country at war. Findings: the social reality that the displaced live in Cali and the possible mechanisms for guiding the attitude and help that can be provided to these olombians who, due to external circumstances, are forced to knock on doors in the hope of finding a final solution to their problem. In addition, it will expand the view of the Colombian vis-a-vis the displaced so that it is no longer a problem that is mentioned in the news, but that once on the street is invisible to the citizen. The State must prepare itself to face the new challenges posed by society, displacement being one of them. Conclusions: the displaced are paid more attention when they flee than when they die.